Apkhazian Writers and Georgia - Nikoleishvili, Avtandil (Actual Problems of Kartvelology, 2025)
While analyzing the attitude of Abkhazian writers towards Georgia, particular attention should be paid to the fact that the topic of Georgia occupied more or less important place in the creative works of every generation representing the XX century Abkhazian literature. The process of gradual and then radical changes in this respect started in 80ies of the previous century. Since this period, one of the noteworthy topics of Abkhazian literature - the well-established pro-Georgian aspiration has started to transform into anti-Georgian hysteria. The majority of Abkhazian writers regard Georgians are the fiercest enemies of Abkhazian people. As the result of Russian purposeful colonial politics, the relationship between Abkhazians and Georgians gradually aggravated and reached the stage where it turned into military conflict in the 90ies of the previous century and terminated with the formation of pseudo-independent republic of Abkhazia. Unfortunately, the majority of Abkhazians, including writers, have not deeply realized that their separation from Georgia and taking this fatal step pose real threats to their national identity. Although the direct influence of Soviet political ideology is reflected in certain part of Abkhazian literature devoted to Georgian theme of Soviet period and the pro-Georgian orientation of the authors is the result of political condition, the love revealed by those writers is so deep that there is no reason to doubt their sincerity. In order to have clearer picture of scales of the abovementioned topics in Abkhazian literature, the article presents detailed analysis the works devoted to Georgian theme by Abkhazian poets (D. Gulia, B. Sinkuba, K. Agumaa, I. Tarba, A. Jonua, K. Lomia, N. Tarba, G. Gurgulia, G. Gublia).